Incorporating Meta‐Atom Interactions in Rapid Optimization of Large‐Scale Disordered Metasurfaces Based on Deep Interactive Learning - Ma, Yihan; Kolb, Jonas Florentin; Ihalage, Achintha Avin; Andy, Andre Sarker; Hao, Yang (Advanced photonics research, 2023)
Surface symmetry breaking and disorder have been recently explored to overcome operation bandwidth, unwanted diffraction, and polarization dependence issues in the conventional metasurface designs thanks to their increasing degrees of design freedom. However, efficient full‐wave simulation and optimization of electrically large electromagnetic structures have been a longstanding problem. Herein, an interactive learning approach is developed to build new meta‐atom datasets which include the effect of mutual coupling. A deep learning‐based model is developed to extract features of incident/reflection waves and their neighboring interaction responses from a limited number of known meta‐atoms. Finally, the deep neural network is incorporated with optimization algorithms to design, as an example, large‐scale metasurfaces for beam manipulation and wideband scattering reduction. The results demonstrate that the proposed architecture can be successfully applied to rapidly design aperture‐efficient metasurfaces or metalenses at large scales of over tens of thousands of meta‐atoms. Herein, the authors propose and demonstrate a novel framework to quantify the influence of mutual coupling between meta‐atoms. By incorporating the deep neural network with optimization algorithm, the proposed architecture can achieve rapid design on the nonperiodic metasurfaces. The design of large‐scale metasurfaces for beam optimization and radar cross‐section reduction has been verified.